(untitled) (Raparin Journal of Humanities (RJH), 2026)
This study aims to clarify and analyze the relationship between green marketing, as the independent variable, and strategic awareness as the dependent variable, through a field study conducted at the University of Raparin, a public university located in the Kurdistan Region of Iraq. Green marketing was examined through several dimensions, including waste elimination or reduction, redesigning the product/service concept, and clarifying the relationship between price and cost. Strategic awareness included both internal and external dimensions. Data were collected using a questionnaire distributed to a sample of administrators, academics, and students. Out of 470 questionnaires distributed, 405 were returned, and 383 were deemed valid for analysis. The study adopted a descriptive-analytical approach using various statistical tools through Excel and SPSS to test the hypotheses. The results revealed a statistically significant positive correlation between green marketing and strategic awareness at both the overall and dimensional levels. This indicates that adopting green marketing practices enhances individuals’ awareness of environmental dimensions and supports sustainability-based strategic planning. The study recommends adopting green marketing as a strategic tool within the educational policies of the University of Raparin and integrating strategic awareness as a core element in developing sustainable institutional performance. It also calls for future comparative studies across different sectors and proposes a long-term practical model that integrates environmental management and green marketing to build a smart and green university environment.